Determining the Ability of an At-home Test Kit to Detect Lead in Drinking Fountains at East Carolina University - Jones, Megan (East Carolina University, 2022)
Lead and other contaminants in drinking water still pose as an important problem in today’s society and can have detrimental effects on human health. At-home water testing kits can offer consumers an easy and affordable way to evaluate their risk, but their accuracy and reliability is still uncertain. This study examined the ability of the AquaScreen Drinking Water Test Kit to detect lead, among other contaminants, in drinking fountain water at East Carolina University. The results were inconclusive as many of the tests were contradicting and had results that were hard to discern. The results highlight areas for possible improvement and suggest that several changes need to be made to at-home water testing kits in order to make them more reliable.
Keywords: lead; water contamination; testing kit